The Use of Bioactive Neem For Preparation Anti Insects - Eddy Sapto Hartanto; Tiurlan Farida Hutajulu (Balai Besar Industri Agro, 2012)
Nowadays, the use of natural plant source insecticides in one of the best chosen due to its characteristic, which of safer and easily degradable by nature (biodegradable) compared to synthetic materials. One of plant sources wiich consists of active components for insecticides is neem plant. This study aimed to determine the effect of extraction of active ingredients of neem seeds and leaves by fermentation using Effective Microorganisms (EM4). The Extraction of seed and leaf neem to produce neem's active compound was conducted by using Effective Microorganisms. The efficacy test of the neem seed and leaf was conducted by using fermented extract concentrated of 3% and 6% and observed with interval of 2 to 6 days. The formula used in this experiment which A as raw material and B as concentration of Effective Microorganisms are A1 as neem;s seed, A2 as neem's leaves; and B as concentration of effective microorganisms which is B1 as 3 %, concentration and B2 as 6 % concentration. The extraction product were evaporated with rotary vacuum evaporator. The extracts obtained were tested their solubility. Azadirachtin were obtained on combination od A1B2 for neem,s seeds for 6 days fermentation period which acquired 1313,23 ppm (61,25 %) of azadirachtin and combination of A2B2 for neem;s leaves which acquired 665,69 ppm (69,17%) of azadirachtin from raw materials. The active compounds were tested their ability as insecticide and showed that 50 ppm of azadirachtin concentration still effective for 14 days evaluation.